2003
DOI: 10.1007/bf02931379
|View full text |Cite
|
Sign up to set email alerts
|

Role of T cells in the adjuvant effect ofbacillus firmus on the immune system of mice: Intranasal and intratracheal immunization study with ovalbumin

Abstract: Functions of T cells were determined after intranasal and intratracheal immunization of mice with ovalbumin (Ova) and Bacillus firmus (Bf), a Gram-positive nonpathogenic bacterium of the external environment, or delipidated Bf (dBf) as adjuvants, with the aim to elucidate the mechanism of support of Ova-specific antibody production caused by Bf that had been observed in an identical experiment. Neither Bf nor dBf in a mixture with Ova stimulated Ova-specific T-cell response tested as antigen-specific blast tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This bacterium is absolutely harmless, inactivated bacteria do not lower the viability of cells in tissue culture and mice tolerate very well high doses of both inactivated and live bacteria [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is absolutely harmless, inactivated bacteria do not lower the viability of cells in tissue culture and mice tolerate very well high doses of both inactivated and live bacteria [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This is the result of a specific antibody response. Our previous studies showed that, in concentrations used in vivo, BF does not cause polyclonal activation of B lymphocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated RNA was treated with RNase-free DNase (Qiagen) and stored in aliquots at −70 • C. RNA integrity and yield were assessed by UV spectrophotometry (Thermo spectronic-Biomate 5) and ethidium bromide staining. DNase-treated RNA was reversetranscribed with oligo(dT) 23 primers using enhanced avian HS RT-PCR kit (Sigma). PCR amplification was performed with specific primers (IL-2, IL-4, IL-10, INF-␥, ␤-actin and iNOS), PCR buffer (Sigma) and HotStartTaq polymerase (Qiagen) in 35 cycles.…”
Section: Rt-pcrmentioning
confidence: 99%